(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2015)
The physical and mechanical properties of rubber (Hevea brasiliensis) wood of Bangladesh of 20, 25 and 30-year age groups were studied. The moisture content of rubber wood was 63% and volumetric shrinkage was 7.43%. The green density and air-dry (12% moisture content) density of rubber wood from 30 years age class was 570 and 590 l.c./m3. Significant difference in moisture content, shrinkage and density was found among the different age classes and height positions. However, longitudinal shrinkage did not vary among the age classes. The MOE and MOR values (air dried) of rubber wood from 30 years age class was 9200 and 65.33 MPa. In most conditions, significant difference with age class and height positions was observed for mechanical properties. The maximum values were found at the bottom position of 30 years age group. On the other hand, the lowest values were observed in the top position of 20 years age group. The strength properties were lower than teak (Tectona grandis), but some strength properties were higher than mahogany (Switenia macrophylla). DOI: http://dx.doi.org/10.3329/bjsir.v49i2.22000 Bangladesh J. Sci. Ind. Res. 49(2), 79-84, 2014